OVERBURDEN TREATMENT TECHNOLOGY IN ACID MINE DRAINAGE PREVENTION - ALI RAHMAT KURNIAWAN; Retno damayanti (Puslitbang tekMIRA, 2007)
The prevention and control of acid drainage is a major issue for mine operators at sites where sulfide minerals occur. On going risk assessment of acid drainage potential and sulfidic waste management during planning, development, operation and closure of mining developments will result in substantial environmental and economic benefits. Overburden treatment technology must be identified and imple- mented in order to minimize the production of acid mine drainage (AMD). There are many treatment technologies for AMD prevention at surface mining such as alkaline addition and special handling. Overburden analysis (OBA) refers to determination of the acidity or alkalinity producing potential. The addition of alkaline material to surface mine backfill can be an effective method of compensating for overburden and reduce the potential for acid mine drainage. Special handling methods fall into four categories: blending, encapsulation, submergence and alkaline redistribution. Special handling is most effective in conjunction with other best management practices such as alkaline addition. Moni- toring during and after mining is necessary to evaluate special handling techniques.